Impact of COVID-19 on Cognitive and Way to Resolve - Azizur Rahman, Mohammad; Rahman, Nabidur (International Journal of Coronaviruses, 2021)
Cognitive abilities are of immense importance for the normal life sustenance of a human being. As cognitive impairment ensues, the living caliber declines. Among multiple factors, the current epidemic coronavirus diseases 2019 (COVID-19) has been implicated in worsening cognitive performance of the COVID-19 sufferers. Present article pinpoints the etiology and patho physiology as well as recommendations to overcome the COVID-19 led cognitive decline.
Keywords: Alzheimer’s disease; Cognition; COVID-19; Dementia; SARS-CoV-2.